2022
DOI: 10.1111/wvn.12565
|View full text |Cite
|
Sign up to set email alerts
|

Engaging advanced practice nurses in evidence‐based practice: An e‐mentoring program

Abstract: Background Mentoring is highly valued in the nursing profession and essential to building an evidence‐based practice (EBP) culture. However, many organizations have a limited number of EBP mentors, who have limited non‐clinical time to engage in mentoring. Aims This project aimed to test whether an e‐mentoring approach to nursing inquiry could enhance EBP beliefs (EBPB), increase EBP Implementation (EBPI), and improve Organizational Culture and Readiness for System‐Wide Implementation of EBP (OCRSIEP). Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(36 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…High-quality evidence syntheses 6. Ongoing surveys and opportunities for feedback Quantitative: -Perceptions of leadership, governance, resource allocation, collaboration and engagement (Partnership survey) Qualitative: -Implementation and impact of projects (project evaluations) -Experiences and perceptions (semi-structured interviews) Partners reported: -Translation of research into policy was built into processes -Many projects involved partners from different sectors -Communication across sectors and teams was adequate -Capacity building activities were valuable -Synergies were identified across projects Moderate (Case report) Hitch, 2019 [ 54 ] Case report, no comparator Public mental health service, major city in Australia, 2014–2016 Occupational therapy Occupational therapists within the organization Leadership role in KT established to support EIDM, complete research projects, build research capacity and culture, and create a database of research activity Quantitative: -Attitudes towards EIDM (Evidence Based Practice Attitude Scale) -EIDM use (Evidence Based Practice Implementation Scale) -Staff perceptions of the Lead Research Occupational therapist role (survey) After implementation of the KT role, -number of quality assurance and research activities increased (Cliffs Delta = 0.44; 95% CI = 0.22, 0.62) -no significant change in attitudes towards EIDM -staff viewed KT role positively -staff engaged in KT activities -greater diffusion of evidence across programs Moderate (Case report) Hooge, 2022 [ 55 ] Single group pre-post study Large academic health system, southeast region, USA, 12-week program; dates not specified Primary care 11 Advanced practice registered nurses Virtual mentoring program delivered via Microsoft Teams platform included synchronous training sessions, podcasts, blog and video tutorials, and additional research articles and educational material Quantitative: -Knowledge and skill for EIDM (Evidence-based Practice Beliefs scale, Evidence-based Practice Implementation scale) -Organizational readiness for EIDM (Organizational Culture and Readiness for System-wide Integration of Evidence-based Practice scale) Qualitative -EIDM facilitators and barriers (open-ended survey) Compared to baseline, evidence-based practice beliefs scores increased (effect size = 0.71, p = 0.018). No significant change in evidence-based practice implementation and organizational culture and readiness for system-wide implementation of evid...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…High-quality evidence syntheses 6. Ongoing surveys and opportunities for feedback Quantitative: -Perceptions of leadership, governance, resource allocation, collaboration and engagement (Partnership survey) Qualitative: -Implementation and impact of projects (project evaluations) -Experiences and perceptions (semi-structured interviews) Partners reported: -Translation of research into policy was built into processes -Many projects involved partners from different sectors -Communication across sectors and teams was adequate -Capacity building activities were valuable -Synergies were identified across projects Moderate (Case report) Hitch, 2019 [ 54 ] Case report, no comparator Public mental health service, major city in Australia, 2014–2016 Occupational therapy Occupational therapists within the organization Leadership role in KT established to support EIDM, complete research projects, build research capacity and culture, and create a database of research activity Quantitative: -Attitudes towards EIDM (Evidence Based Practice Attitude Scale) -EIDM use (Evidence Based Practice Implementation Scale) -Staff perceptions of the Lead Research Occupational therapist role (survey) After implementation of the KT role, -number of quality assurance and research activities increased (Cliffs Delta = 0.44; 95% CI = 0.22, 0.62) -no significant change in attitudes towards EIDM -staff viewed KT role positively -staff engaged in KT activities -greater diffusion of evidence across programs Moderate (Case report) Hooge, 2022 [ 55 ] Single group pre-post study Large academic health system, southeast region, USA, 12-week program; dates not specified Primary care 11 Advanced practice registered nurses Virtual mentoring program delivered via Microsoft Teams platform included synchronous training sessions, podcasts, blog and video tutorials, and additional research articles and educational material Quantitative: -Knowledge and skill for EIDM (Evidence-based Practice Beliefs scale, Evidence-based Practice Implementation scale) -Organizational readiness for EIDM (Organizational Culture and Readiness for System-wide Integration of Evidence-based Practice scale) Qualitative -EIDM facilitators and barriers (open-ended survey) Compared to baseline, evidence-based practice beliefs scores increased (effect size = 0.71, p = 0.018). No significant change in evidence-based practice implementation and organizational culture and readiness for system-wide implementation of evid...…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge Broker strategies were mostly implemented in parallel with other EIDM implementation strategies, such as capacity building for staff, integrating EIDM into decision-making processes and development of leadership to support EIDM. When these strategies were evaluated quantitatively for organizational capacity, culture and implementation of EIDM, most studies found positive results, such as increased scores for organizational climates supporting EIDM, improved attitudes toward EIDM, or the integration of EIDM into processes [ 44 , 52 , 54 , 62 , 66 , 67 , 71 , 72 ], although some studies found no change [ 55 , 60 ] following implementation of Knowledge Broker roles. Qualitatively, most studies described facilitators and barriers to EIDM, either through formal qualitative analysis or case report [ 14 , 20 , 39 43 , 45 , 47 , 48 , 52 , 55 , 57 , 59 61 , 64 , 65 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The OCRSIEP identifies organizational characteristics, including strengths and opportunities, for enhancing consistent implementation of EBP by clinicians within a healthcare system. The scale has been used in a variety of populations, has established face and content validity, and consistent internal consistency reliabilities (Cleary‐Holdforth et al, 2021; Hooge et al, 2022; Melnyk et al, 2016, 2020), but has yet to have construct validity thoroughly assessed. Thus, this study aimed to describe the OCRSIEP's construct validity through an in‐depth psychometric analysis that included exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and fit indices.…”
Section: Introductionmentioning
confidence: 99%
“…When these strategies were evaluated quantitatively for organizational capacity, culture and implementation of EIDM, most studies found positive results, such as increased scores for organizational climates supporting EIDM, improved attitudes toward EIDM, or the integration of EIDM into processes(51, 54, 56, 59-61, 64, 65), although some studies found no change(53, 58) following implementation of Knowledge Broker roles. Qualitatively, most studies described facilitators and barriers to EIDM, either through formal qualitative analysis or case report(5, 46,49,50,52,53,57, 58, 62, 64,(66)(67)(68)(69)(70)(71)(72)(73)(74) Facilitators included organizational culture with supportive leadership and staff buy-in, expectations to use evidence to inform decisions, accessible knowledge, and integration of EIDM into processes and templates. Barriers included limited time and competing priorities, staff turnover, and lack of understanding and support from management.Ten included studies focused primarily on building EIDM capacity of existing staff at the organization, often at multiple levels (e.g., front-line service providers, managers, and leadership)(4, 5, 68,70,71,(73)(74)(75)(76)(77)(78).…”
mentioning
confidence: 99%